Wage Dispersion in Russia - L.A. Grogan (Tinbergen Institute, 1997)
This paper examines the extent to which human capital theory can explain observed wage differentialsin the Russian Federation. Wage and income dispersion have increased markedly in Russia in the sixyears since the transition began. Some studies conclude that this is an indicator that Russian labourmarkets are becoming more competitive. In this paper, this conclusion is scrutinised from theperspective of human capital theory. Human capital theory predicts that, in unregulated labour markets,workers' remuneration depends on their individual productivity, which is itself a function ofexperience, education and skill levels, and occupation type. According to this theory, the deregulationof Russian labour markets in the transition to a market economy should make observed wages moredependent on these factors. The extent to which human capital factors influence wages can be viewed asan indicator that labour markets are beginning to 'work'. We use cross-sectional data from theGoskomstat Russian Longitudinal Monitoring Survey to characterise wage dispersion in the Russianlabour market in 1994. The results suggest that human capital variables explain only a small portion ofRussian wage differentials. Much more of Russian wage dispersion can be explained by regional andgender-based wage differentials. Labour markets are effectively segregated by region. This analysisconcludes that increased Russian wage dispersion does not indicate that the Russian labour market isbecoming more competitive.Theme: Transitions in the Labour Market in Eastern Europe
Keywords: J31; O52; P11; J16; 330; Russia; human capital; wage dispersion; Lohnstruktur; Humankapital; Lohnstruktur; Übergangswirtschaft; Russland